EXPERIENCE OF SEXUAL DISFUNCTION IN MEN CLIENTS WITH DIABETIC ULCERS - maulida, haifah (Jurnal Persatuan Perawat Nasional Indonesia (JPPNI), 2019)
The prevalence of diabetes mellitus in the world is getting increased either developed or developing countries, it will lead the complication toward one of sexual activity. The aim of this research to find in depth about sexual disfunction with Diabetic ulcers patient experiance. This research used a qualitative method with a phenomenological approach and interview as collacting data technique. Therewere 7 informants, with 6 item of experiance question those are (1) sexual views in men, (2) description of sexual changes, (3) the impact of sexual change, (4) how to overcome problems, (5) expectations of condition, (6) response from system support. The results of this study are known that diabetes mellitus clients who experience sexual dysfunction that affects themselves and couple, clients look for ways to deal with their perceptions, expect conditions for sexual change in themselves and couple, and expect support from spouses and families to improve sexual function.